Marinella Arena (2023). Città sospese fra capi e fiumare. Strategie identitarie. Milano: FrancoAngeli (diségno, 2024)
The book by Marinella Arena deals with a crucial topic. Essential. Not only in the subject of her research (historic villages in a state of ‘oblivion’), but also –and above all– in the gaze she reserves for small towns, specifically those on the Ionian coast of Sicily. A gaze able to interweave the urban and architectural survey with the immaterial dimensions of which these centers are permeated, through a vision that includes different perceptive levels. A deep interpretation, carried out with the sensitivity that derives from personal experiences, from the cultural context, from immersion in a ‘scenery of everyday life’ that, as the author emphasizes, has (successfully) conditioned her approach to research. [read more]